From Biting to Hugging : Understanding Social Development in Infants and Toddlers. - Wittmer, Donna (Gryphon House Inc., 2018)
With the increase in both parents working outside the home during the last two decades, infants and toddlers are spending more time together in infant/toddler programs and family child-care homes. From Biting to Hugging will give you effective strategies to help you take advantage of this peer time.
Keywords: Early childhood education -- Social aspects.; Social interaction in infants.; Social interaction in children.; Infants -- Development.; Toddlers -- Development.; Éducation de la première enfance -- Aspect social.; Interaction sociale chez le nourrisson.; Interaction sociale chez l'enfant.; Nourrissons -- Développement.; Tout-petits -- Développement.; EDUCATION -- Elementary.; Early childhood education -- Social aspects; Infants -- Development; Social interaction in children; Social interaction in infants; Toddlers -- Development